Pengaruh Latihan Shuttle Run terhadap Hasil Tendangan Karate Siswa di SMP Swasta Primbanana Medan Tahun 2023 - Ardilla, Rafika; Hutasoit, Ricky (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the effect of shuttle run exercises on karate mawasi kicks on extracurricular activities of SMP Swasta Primbanan. The research method used is experimental quasy with pretest-posttes one group design design. The population in this study are students who follow karate, the sample in this study amounted to 30 people. The research instrument used was a mawasi kick test. Treatment in this research is the exercise of shuttle run given for 6 weeks with frequency of exercise for a week 3 times. The effectiveness test using experimental method with the result of "t test" significant α = 0,05 got tcount = (11,3) while ttable = (1,70), then tcount> ttable means thitung> ttable so Ha is acceptable, while Ho is rejected . Based on the research findings that Ha is acceptable, the shuttle run exercise has an effect on the mawasi kick. The implication of this research is that the shuttle run exercise can be used as one type of exercise to for the result of a mawasi kick.